2005
DOI: 10.1590/s0034-72992005000400007
|View full text |Cite
|
Sign up to set email alerts
|

Reabilitação vestibular personalizada: levantamento de prontuários dos pacientes atendidos no ambulatório de otoneurologia da I.S.C.M.S.P.

Abstract: O OBJETIVO: o objetivo deste trabalho foi verificar a eficácia da reabilitação vestibular personalizada (RVP) em diferentes quadros otoneurológicos. FORMA DE ESTUDO: clínico retrospectivo. MATERIAL E MÉTODO: Foi realizado um estudo retrospectivo que constou de uma descrição do programa de reabilitação vestibular de 37 pacientes, com idade entre 21 a 87 anos, vinte e seis do sexo feminino, onze do sexo masculino, com quadros otoneurológicos variados, atendidos no Ambulatório de Otoneurologia do Departamento de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
15
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 4 publications
4
15
0
8
Order By: Relevance
“…The analysis of electronystagmography according to sex ( Table 2) revealed results that are similar to those presented by Resende et al, 2 Simoceli et al, 16 Moreira et al, 19 Nishimo et al, 20 and Traldi et al, 22 who showed the prevalence of altered otoneurological results in females.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The analysis of electronystagmography according to sex ( Table 2) revealed results that are similar to those presented by Resende et al, 2 Simoceli et al, 16 Moreira et al, 19 Nishimo et al, 20 and Traldi et al, 22 who showed the prevalence of altered otoneurological results in females.…”
Section: Discussionsupporting
confidence: 81%
“…These results confirm VR as an effective treatment for reducing dizziness and improving the quality of life of patients. 1,3,20,21,22 The relation between otoneurological evaluation results and VR shows that significant and partial improvement was more evident in patients with peripheral otoneurological alterations (Table 6), which is similar to the findings of Telian and Shepard. 18 These authors demonstrated that the best results of VR may be seen in patients with incomplete or decompensated unilateral peripheral lesions.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Os principais recursos fisioterapêuticos utilizados no estudo foram descritos e fundamentados conforme referenciais e, da mesma forma como acima, outros estudos sempre estão disponíveis e não foram citados no trabalho original, como o de Nishino et al 5 .…”
unclassified